Arthroscopy of the Knee Joint - Gallannaugh, S. (1973)
Review of the results of arthroscopy of the knee joint in a consecutive series of 112 patients showed that in 81 knees the preoperative diagnosis was confirmed, and in 24 it was found to be incorrect. In seven knees the procedure yielded no further information owing to poor visualization within the joint. Arthroscopy provides a useful means of achieving more accurate diagnosis in patients with internal derangements of the knee.